Deletion of Multispecific Organic Anion Transporter Oat1/Slc22a6 Protects against Mercury-induced Kidney Injury - Torres, Adriana M. (American Society for Biochemistry and Molecular Biology, 2011)
The primary site of mercury-induced injury is the kidney due to uptake of the reactive Hg(2+)-conjugated organic anions in the proximal tubule. Here, we investigated the in vivo role of Oat1 (organic anion transporter 1; originally NKT (Lopez-Nieto, C. E., You, G., Bush, K. T., Barros, E. J., Beier, D. R., and Nigam, S. K. (1997) J. Biol. Chem. 272, 6471–6478)) in handling of known nephrotoxic doses of HgCl(2). Oat1 (Slc22a6) is a multispecific organic anion drug transporter that is expressed on the basolateral aspects of renal proximal tubule cells and that mediates the initial steps of elimination of a broad range of endogenous metabolites and commonly prescribed pharmaceuticals. Mercury-induced nephrotoxicity was observed in a wild-type model. We then used the Oat1 knock-out to determine in vivo whether the renal injury effects of mercury are mediated by Oat1. Most of the renal injury (both histologically and biochemically as measured by blood urea nitrogen and creatinine) was abolished following HgCl(2) treatment of Oat1 knock-outs. Thus, acute kidney injury by HgCl(2) was found to be mediated mainly by Oat1. Our findings raise the possibility that pharmacological modulation of the expression and/or function of Oat1 might be an effective therapeutic strategy for reducing renal injury by mercury. This is one of the most striking phenotypes so far identified in the Oat1 knock-out. (Eraly, S. A., Vallon, V., Vaughn, D. A., Gangoiti, J. A., Richter, K., Nagle, M., Monte, J. C., Rieg, T., Truong, D. M., Long, J. M., Barshop, B. A., Kaler, G., and Nigam, S. K. (2006) J. Biol. Chem. 281, 5072–5083).